PENGARUH PENGERINGAN TERHADAP PERUBAHAN WARNA, PENYUSUTAN TEBAL, DAN PENGURANGAN BERAT EMPAT JENIS BAMBU - Adik Bahanawan; Krisdianto (BRIN Publishing, 2020)
The surface color of bamboo stem changes naturally due to surrounding conditions. This paper studies the changesin bamboo surfaces color due to room temperature drying (KU) and oven drying (KO) at 60±2 °C. The color changesof four bamboo species: mayan (Gigantochloa robusta Kurz.), ater (Gigantochloa atter (Hassk) Kurz. Ex.Munro), ampel kuning (Bambusa vulgaris var. striata), and wulung (Gigantochloa atroviolacea Widjaja) werestudied together with their correlation to water loss. Color measurements were conducted based on CIE-Lab system,while water content related to weight loss and thickness shrinkage during KU and KO. The result showed that therewas a close relationship between water loss and discolouration of bamboo culms. The water loss of mayan, ater, andwulung showed a positive linear correlation to change of bamboo surfaces color, where the higher water loss affect greatervalue of color change too. Oppositely, in ampel kuning, higher water loss, affect smaller color change value (negativelycorrelated). This was because the natural color of ampel kuning in fresh conditions is not much different from colorafter drying. KU treatments, biggest thickness shrinkage was mayan = 46.03%; biggest weight reduction was ampelkuning = 28.52%; and biggest color changes (ΔE*) was ater = 15.51%. KO treatments, biggest thickness shrinkagewas mayan = 52.4%; biggest weight reduction was yellow ampel = 31.19%; and biggest color changes (ΔE*) wasater = 18.8%.